2015
DOI: 10.20510/ukjpb/3/i6/87836
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening and Antibacterial Activity of Ethanol Extract of Leaves and Twigs of Azadirachta indica A. Juss

Abstract: Azadiracheta indica A. Juss commonly known as Neem belongs to family Meliaceae. Each part of A. indica has been used extensively for various ailments. In the present study A. indica leaves and twigs were shade dried and made into powder. This powdered material was subjected for extraction using ethanol (10gm powder in 100ml ethanol). Ethanol extracts (EE) of leaves and twigs were qualitatively screened for the presence of phytochemicals viz. alkaloids, flavonoids, saponins, tannins, polyphenols and steroids. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…aureus whereas MIC values were comparable in case of E . coli (Ravi, Bharavi, Ravi Kumar, & Vamsi, ). It was reported that bactericidal potential of ethyl acetate extract of leaves (100 μg/ml) was similar to the standard, ciprofloxacin when evaluated against Campylobacter jejuni and Leuconostoc sp .…”
Section: Pharmacological Attributesmentioning
confidence: 99%
“…aureus whereas MIC values were comparable in case of E . coli (Ravi, Bharavi, Ravi Kumar, & Vamsi, ). It was reported that bactericidal potential of ethyl acetate extract of leaves (100 μg/ml) was similar to the standard, ciprofloxacin when evaluated against Campylobacter jejuni and Leuconostoc sp .…”
Section: Pharmacological Attributesmentioning
confidence: 99%
“…Raf Kinase Inhibition: The 3D QSAR analysis for amino-substituted N-acetyl and N-aroylpyrazolines 26 as B-Raf kinase inhibitors was performed by Omprakash Tanwar et al 28 , using a common fivepoint pharmacophore modal. The B-Raf inhibitory activity of selected compounds was investigated by Blackburn et al 29 from a large screening library of n an N-acetyl and N-aroylpyrazolines 27.…”
Section: Acetyl Cholinesterase Inhibitory Activitymentioning
confidence: 99%
“…Qualitative chemical tests were performed to determine the presence of alkaloids, carbohydrates, cardiac glycosides, polyphenols, saponins, tannins and terpenoids [14][15][16][17] . …”
Section: Preliminary Phytochemical Tests Of Oilmentioning
confidence: 99%